Chronic polyarthritis mimicking rheumatoid arthritis in a patient with leprosy - A S Haribowo; Bagus Putu Putra Suryana; Kusworini Handono (Indonesian Journal of Rheumatology, 2009)
Currently leprosy is now still a global threat in the world even after the introduction of multidrug therapy (MDT), including in Indonesia.1 World Health Organization (WHO) data revealed that in 2002 there were 597,000 cases worldwide and the prevalence is only less than 1 every 10,000 populations.2 Nevertheless, the latest data showedthat 83% of leprosy cases concentrated in only 6 countries: Indonesia, India, Brazil, Madagascar, Myanmar, and Nepal.3 The most common manifestations of leprosyare cutaneous and neuritic manifestation. Rheumatologic manifestation is another common manifestation of leprosy.4-7 Prevalence of rheumatologic manifestation of leprosy is range from 1% to 77% of all leprosy patients.4-11 Study conducted by Mandal et al in India revealed that the prevalence of rheumatologic manifestation was 5.9%, in Brazil,6 another study by Pereira revealed the prevalence of 9.1%.5 Hadi, in Indonesia,showed the prevalence of arthritic manifestation was 7.5%.8 RheumatologicÂ  manifestations that can be found in leprosy are polyarthritis or oligoarthritis, soft tissue rheumatism, noninflammatory arthritis, and also enthesitis.4-7 We report a patient presenting with polyarthritis as the primary manifestation of leprosy.